BOOK REVIEW OF THE BOURNE BETRAYAL WRITTEN BY ERIC VAN LUSTBADER - Ananda, Jordy Dio (LANTERN (Journal on English Language, Culture and Literature), 2016)
The purposes of this final project is to study about book review of The Bourne Betrayal novel book. The Bourne Betrayal is the fifth book of Jason Bourne novel series who is the original author Robert Ludlum and continued by Eric Van Lustbader. The genre of this book is thriller-action and adventure. In this final project I will discuss about the profile of the author of The Bourne Betrayal novel book, the summary of the book, the strengths and the weaknesses. This book review may help for people who is have a big interest of Jason Bourne story.